Microstructural evolutions of the Al strip prepared by cold rolling and continuous equal channel angular pressing - Lee, JC; Seok, HK; Suh, JY (PERGAMON-ELSEVIER SCIENCE LTD, 2002)
A new metal forming technique termed the continuous confined strip shearing (C2S2) process based on equal channel angular pressing (ECAP) is introduced. Unlike the conventional batch-type ECAP process dealt in the earlier studies, the developed technique enables sheet forming in a continuous mode and in a repeatable manner. Likewise rolling, the developed process is able to control the mechanical properties of the material through the multipass operation. Both hardening and softening mechanisms in ECAP were investigated by correlating the measured hardness with microstructural evolutions of the Al specimens using transmission electron microscopy. The process conditions required to produce the fine-grained structure were suggested in terms of the strain per passage and the total strain imparted to the specimens. The effect of the temperature on the accelerated grain refining during the continuous ECAP operation was discussed. (C) 2002 Published by Elsevier Science Ltd on behalf of Acta Materialia Inc.
Keywords: DEFORMATION-BEHAVIOR; SHEAR DEFORMATION; ALLOY